KONDISI PERAIRAN DAN POTENSI KEPITING BAKAU (Scylla sp) DI KECAMATAN ALUH-ALUH KALIMANTAN SELATAN - Junius Akbar (EnviroScienteae, 2011)
The purpose of the research was to give information condition and potention of mud crab. This research used survey method which are a). observation, b). direct interview c). in situ treatment and d). sampling.  Research location at Sungai Musang Village, Aluh-Aluh, Banjar Regency, South Kalimantan Province. Parameters observe were mud crab species, water quality (water temperature, salinity, water pH, NO2-N, NO3-N, NH3-N, DO, and transfarance), and biology (plankton dan mud crab larvae). The results founded that 3 mud crab species 1). Scylla serrata 2). S. transquebarica and  3) S. oceanica. The range of water temperature was (30-340C), Salinity (0-1%o), water pH (7,80-8), NO2-N (0,36 mg/L), NO3-N (2,01 mg/L), NH3-N (0,46-2,5 mg/L), DO (1,65-4,20 ppm), transparance (32 cm), diversity index of phytoplankton (0,89), and  zooplankton (1,58).  Ecology and biology, showed that water quality was suitable to mud crab culture. Mud crab larvae was trap zoae and megalopa stadia with density of 20 ind/L. Little number of mud crab trapped, was assumed due todisfunction condition of  mangrove forest.